Estradiol Alleviates Intervertebral Disc Degeneration through Modulating the Antioxidant Enzymes and Inhibiting Autophagy in the Model of Menopause Rats. (23rd December 2018) - Jin, Lin-Yu; Lv, Zhen-Dong; Wang, Kun; Qian, Lie; Song, Xiao-Xing; Li, Xin-Feng; Shen, Hong-Xing
Abstract : Objective . To investigate the effects of menopause on redox balance in the intervertebral disc and to examine whether oxidative stress and autophagy were associated with disc degeneration in menopause rats. Methods . Thirty female Sprague-Dawley rats were randomly divided into three groups (sham, ovariectomized with vehicle, and ovariectomized with estrogen). At the end of the 3-month treatment, the rats were examined by 3.0 T MRI. Serum estradiol (E2) level was measured. Redox balance of nucleus pulposus was determined by measuring total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione (GSH), and oxidized glutathione (GSSG). Transmission electron microscopy (TEM), immunohistochemical staining, and Western blot were used to determine the nucleus pulposus autophagy level. At the same time, Spearman's correlation coefficient was used to describe the relationship between intervertebral disc grade, oxidative stress status, serum E2, and autophagy level. Results . The level of serum E2 was significantly decreased by ovariectomy and can be corrected by the estrogen replacement therapy (ERT). In OVX rats, an increased oxidative stress and high level of autophagy were observed in nucleus pulposus tissue. ERT prevented the intervertebral disc degeneration (IVDD), restored the redox balance, and reduced autophagy level. Conclusion . Ovariectomy induced oxidative stress, autophagy, and intervertebral disc degeneration. Autophagy of the intervertebral disc was negatively correlated with oxidative stress, and the level of autophagy can be reduced by ERT through modulating the redox balance and downregulating the autophagy level. Regulating the redox balance of IVD may be a potential therapeutic option for degeneration of the disc in the postmenopausal women.